(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2020)
This research deals with the means of modern technology and their impact on worships, using purity and prayer as a model, and among its objectives that it sought to achieve: Determine the type of blood flowing to women through the use of modern technology and medical tests, prove puberty by analyzing blood by means of modern technology, statement of permissibility The use of modern technology means in determining the qiblah, and I have followed the descriptive and analytical approach through the legal texts of the Qur’an, the authentic Sunnah and the sayings of the jurists, and the research reached a set of results and recommendations, including: - That what is meant by the means of modern technology are all the methods and things that a person uses and invents to meet his needs and satisfy his desires. - The results of the samples that tell that the blood that occurs to a woman who is starting is menstrual blood will be considered if these samples were performed by a reliable medical device. As for the recommendations, they include: Publishing the decisions and opinions reached by the Fiqh Councils on the ruling on using modern technology in worship and other things. Holding scientific conferences and forums, issuing periodicals and electronic publications related to such jurisprudential issues.